Judicialização de direitos sociais: contradições, desafios e potencialidades ao Serviço Social na Defensoria Pública do estado de São Paulo - Castro, Tatiana de Cardoso e Mendes [UNIFESP] (2019)
The judicialization of social rights appears in contemporary times as a right established by the Federal Constitution of 1988, inasmuch as a citizen does not have his right granted, such as access to medicine dispensing, a place in early childhood education, hospital beds, or same public civil action to guarantee the common law to a segment. In this way, the search for judicial resources constitutes a strategy or even a necessity for many people, families and communities against a neoliberal, "minimal" state, scrapped, excluding and violating rights, which does not press for social policies. The growing demand for the Justice System to resolve demands aimed at the realization of social rights reflects one of the possibilities of confronting social inequalities and especially the search for the guarantee of legally foreseen rights, won through struggles and social movements, but not effected. On the other hand, this judicial process, if used interchangeably, corroborates a possible overlapping of the Judiciary Power to the Executive Branch, also contributing to the State's lack of responsibility and depoliticization of the public sphere. In this sense, this Master's Dissertation aims to present the question of the judicialization of social rights such as health, education, social assistance and housing within the Public Defender's Office of the State of São Paulo (DPESP) and the contradictions, challenges and potentialities that put into the daily life of the Social Worker in the Institution, in the attention to the judicialization or not of the demands brought by the individuals who seek the Public Defender's Office. The Social Service works directly in interface with the organs of the System of Guarantee of Rights, so it has theoretical and methodological, technical and operative, ethical and political resources to contribute to the resolution of the problem in an effective and fast way through judicial and extrajudicial mechanisms. The present study was developed in a critical and dialectical perspective of the reality, using a qualitative approach, based on bibliographical, documentary research, data collection of electronic medical records and questionnaires to Social Assistants of the Institution. It is believed that the theme to be studied is complex, paradoxical, instigating and reflects the current societal conjuncture of dismantling rights, precarious social relations and criminalization of poverty. It is an initial study that is not exhaustive, but brings important reflections on the contradictions and potentialities that permeate the search for the effectiveness of rights in the contemporary world.